Conceptual framework on information security risk management in information technology outsourcing / Nik Zulkarnaen Khidzir, Noor Habibah Arshad and Azlinah Mohamed - Khidzir, Nik Zulkarnaen; Arshad, Noor Habibah; Mohamed, Azlinah (CMIWS and UiTM Press, 2010)
Data security and protection are seriously considered as information security risk for information asset in IT outsourcing (ITO). Therefore, risk management and analysis for security management is an approach to determine which security controls are appropriate and cost effective to be implemented across organization for ITO to secure data/information asset. However, previous established approach does not extensively focus into information security risk in ITO. For that reason, a conceptual framework on information security risk management in IT outsourcing (ISRM-ITO) will be introduced throughout this paper. An extensive amount of literature review on fundamental concepts, theoretical background and previous findings on information security risk management and ITO had been conducted. Throughout the review, theoretical foundation and the process that lead to success in managing information security risk ITO were identified and these findings become a key component in developing the conceptual framework. ISRM-ITO conceptual framework consists of two layers. The first layer concentrates on information security risks identification and analysis before the decision is made to outsource it. The second layer will cover the approach of information security risk management which is used to analyze, mitigate and monitor risks for the rest of the ITO lifecycle. Proposed conceptual framework could improve organization practices in information security study for IT outsourcing through the adoption of risk management approach. Finally, an approach to determine a cost effective security control for information security risk can be implemented successfully in the ITO cycle.